Simulation of layered soil water transport in the semi-arid region based on Hydrus-3D - Yingguo Wang; Haiou Zhang; Yingying Sun; Jian Wang; Lei Shi (PLoS ONE, 2025)
This study addresses the unclear water transport patterns in reconstructed layered soils in the arid and semi-arid climate zones of northwestern China by utilizing the Hydrus-3D model to simulate the rainfall infiltration process. Simulation experiments were designed to investigate different configurations of layered soils, with changes in soil moisture profiles monitored throughout. The water transport characteristics of these soils were comprehensively analyzed from four perspectives: soil moisture, water potential, water flux, and lateral flow within the soil. In order to further explore the influence of interlayer properties on shallow soil moisture dynamics, scenario simulations and global sensitivity analysis were conducted based on optimized models. The results demonstrated that interlayers significantly influence soil water distribution and transport patterns. During the rainy season, soil water content and lateral flow decreased with increasing soil depth, whereas these values increased during the dry season, suggesting that deeper soil layers exhibit strong water storage capacities. Both loess and sandy interlayers impeded water infiltration, albeit through different mechanisms. The loess interlayer retained water due to its low permeability, while the sandy interlayer caused water retention in the overlying clay soil as a result of its low matric potential. Based on the simulation outcomes, it is recommended that a 10 cm thick loess interlayer at a depth of 40 cm in sandy soil enhances upper soil moisture availability for vegetation, whereas a 10 cm thick sandy interlayer at the same depth in loess soil improves soil permeability. This study not only advances understanding of the impact of loess infill on soil moisture dynamics in sandy soil regions but also provides critical guidance for soil reconstruction practices in northwestern China, where sandy soils and loess are predominant.